Impact of Age and Level of Experience on Occupational Stress of Academic Managers at Higher Educational Level - Mahmood, Azhar; Zamir, Shazia; Ain, Qurat-ul-; Nudrat, Saira; Zahoor, Fatima (Mediterranean Journal of Social Sciences, 2013)
The present study was aimed to analyze the impact of age and management experience on occupational stress of academicmanagers in Higher Education Institutions of Pakistan. Qualitative and quantitative approaches have been used to explore theimpact of age and management experience of occupational stress by using a sample of 120 academic managers of publicsector institutions of higher education located in Punjab, Pakistan. In order to select representative sample from the population,simple random sampling technique was used .Data were collected through registered mail and personal visits to the offices ofprincipals. Total sample size was 120.For data analysis; both descriptive and inferential statistics were used. Researchinstrument Occupational Stress Inventory–revised (OSI-R) was used to collect data. For data analysis Pearson Correlation andANOVA were applied. Data analysis revealed that significant negative relationship was found in responses of academicmanagers regarding impact of age and management experience on occupational stress. Findings also suggest that there is aconnection between age, management experience and the way stress is perceived.